Nile River Basin Hydrology, Climate and Water Use - Melesse, Assefa M. (Springer Netherlands : Imprint: Springer, 2011)
This book presents results of scientific studies ranging from hydrological modelling to water management and policy issues in the Nile River basin. It examines the physical, hydrometeorological and hydrogeological description of the basin along with analysis in understanding the hydrological processes of the basin under the changing land-use stemming from population pressure and increased natural resources tapping. The book discusses the increased impact of climate change on the river flows, and such issues as water availability and demand, management and policy to offset the imbalance between demand and available resources. Audience This book will be of interest to researchers, practitioners, water resources mangers, policy makers as well as graduate and undergraduate students. It is a useful reference text for ecohydrology, arid zone hydrology, hydrology of transboundary rivers and similar courses.